Efektifitas Penerapan Model Project-Based Learning Berbantuan Autocad Terhadap Kualitas Pembelajaran Gambar Teknik Listrik - Mona Risdiyanti Putri; Aswardi Aswardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This research focuses on increasing students' interest and skills in Electrical Engineering Drawing through the application of the Project-Based Learning learning model with the support of Autocad as a tool. The aim is to overcome obstacles in conventional learning and improve the effectiveness and results of students' practice. This research uses a quasi-experiment approach with a non-equivalent control group pretest-posttest design. The subjects were students of class X TKL 1 and To measure effectiveness, the experimental group was given treatment using the Project-Based Learning learning model assisted by Autocad, while the control group applied the conventional learning model. Psychomotor results will be analyzed through a number of tests, including descriptive, t-test, classical exhaustiveness, and effect size. Based on the research results, it appears that the experimental group using the Project-Based Learning learning model assisted by Autocad had a significantly higher average score (82.89) than the control group (68.53). The standard deviation of the experimental group was also lower, indicating better consistency. In addition, the pass percentage in the experimental group (94.4%) was much higher than the control group (25%). Thus, it can be concluded that the application of this learning model is effective in improving students' practical results in the Electrical Engineering Drawing subject at SMK Negeri 1 Bukittinggi.